INTERAKSI SOSIAL MASYARAKAT ISLAM DAN KRISTEN DI KECAMATAN RANTAU UTARA KABUPATEN LABUHANBATU - Ilham, Novriyal; Irwansyah, Irwansyah; Ismail, Ismail (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This study aims to determine the social interaction of Muslim and Christian communities in Rantau Utara District, Labuhanbatu Regency. The research method uses descriptive qualitative. Data collection techniques use observation, interviews, and documentation. The analysis techniques in this study are data reduction, data presentation, and conclusions. The results showed that harmonious relations between Muslim and Christian communities in Rantau Utara District through various activities, such as gotong royong activities, religious holidays such as Eid al-Fitr, Eid al-Adha, Christmas, and other holidays. The harmonious relationship that occurs among Muslims and Christians in North Rantau District is the existence of activities that become a meeting place between Muslims and non-Muslims. Through these activities, all people, both Muslims and non-Muslims, carry out social interaction. The driving factor for the establishment of social interaction of religious tolerance in North Rantau District is the role of the government and awareness of the village community through programs held by the sub-district so that it can foster a sense of soidity and tolerance with people of other religions. Supporting factors in the harmonious relationship between Muslims and Christians in Sirandorung Village are mutual respect, openness, communication, and inclusivity.